Identifying a list of Salmonella serotypes of concern to target for reducing risk of salmonellosis - Katz, Tatum S.; Harhay, Dayna M.; Schmidt, John W.; Wheeler, Tommy L. (Frontiers in Microbiology, 2024)
There is an increasing awareness in the field of Salmonella epidemiology that focusing control efforts on those serotypes which cause severe human health outcomes, as opposed to broadly targeting all Salmonella, will likely lead to the greatest advances in decreasing the incidence of salmonellosis. Yet, little guidance exists to support validated, scientific selection of target serotypes. The goal of this perspective is to develop an approach to identifying serotypes of greater concern and present a case study using meat-and poultry-attributed outbreaks to examine challenges in developing a standardized framework for defining target serotypes.